2001
DOI: 10.1164/ajrccm.164.1.2011153
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Distribution of Burkholderia cepacia Complex Species and Transmissibility Markers in Cystic Fibrosis

Abstract: Several distinct species (genomovars) comprise bacteria previously identified merely as Burkholderia cepacia. Understanding how these species, collectively referred to as the B. cepacia complex, differ in their epidemiology and pathogenic potential in cystic fibrosis (CF) is important in efforts to refine management strategies. B. cepacia isolates recovered from 606 CF patients receiving care at 132 treatment centers in 105 cities in the United States were assessed to determine species within the B. cepacia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
239
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(254 citation statements)
references
References 23 publications
12
239
1
Order By: Relevance
“…However, it was apparent that not all B. cepacia strains have the same capacity for epidemic cross-infection or are capable of causing fatal pneumonia [8,12,13]. Taxonomic studies have revealed that B. cepacia consists of a group of at least five phenotypically similar and closely related genomic species (B. cepacia genomovars I-V), which has become known as the B. cepacia complex [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was apparent that not all B. cepacia strains have the same capacity for epidemic cross-infection or are capable of causing fatal pneumonia [8,12,13]. Taxonomic studies have revealed that B. cepacia consists of a group of at least five phenotypically similar and closely related genomic species (B. cepacia genomovars I-V), which has become known as the B. cepacia complex [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although all B. cepacia genomovars can colonise CF patients, the large majority of infections is caused by B. multivorans or B. cepacia genomovar III [12,13,27]. The aim of the present study was to evaluate the sensitivity and specificity of recA-based PCR tests for the identification of these B. cepacia genomovars and of PCR tests for B. cepacia genomovar I and B. ambifaria.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory identification of BCC up to genomovar level is also crucial since certain genomovars are reported to be highly transmissible between CF patients and stringent infection control policies should be undertaken to prevent transmission to other patients [1,8,11]. The discrepancy between results obtained by phenotypic and molecular detection techniques is also of importance for the identification of BCC.…”
Section: Discussionmentioning
confidence: 99%
“…cenocepacia and Burkholderia multivorans are the most frequently isolated Bcc species from CF patients (Govan et al, 2007;LiPuma, 2005;Reik et al, 2005). B. cenocepacia accounts for most transmissible strains, although transmissible strains of B. multivorans and Burkholderia dolosa have also been reported in some CF centres (Biddick et al, 2003;LiPuma et al, 2001;McDowell et al, 2004;Speert et al, 2002). CF patients infected with B. cenocepacia have a much lower success rate after lung transplantation compared to CF patients infected with other Bcc species or not infected with Bcc (Alexander et al, 2008;Murray et al, 2008).…”
Section: Introductionmentioning
confidence: 99%